A thin film composite membrane supported by a hydrophilic poly(vinyl alcohol‐co‐ethylene) nanofiber membrane: Preparation, characterization, and application in nanofiltration. Issue 19 (1st February 2018) - Li, Ruipeng; Li, Mufang; Li, Zheng; Zhu, Qing; Zhong, Weibing; Liu, Ke; Wang, Dong
ABSTRACT: In this study, a fabricated hydrophilic poly(vinyl alcohol‐ co ‐ethylene) (PVA‐ co ‐PE) nanofiber membrane was used as the middle support layer to prepare thin film composite (TFC) membranes for nanofiltration. The effects of the supporting nonwoven layer, grams per square meter (GSM) of nanofiber, reaction time, heat treatment, monomer concentration, operating pressure, and pH value on the separation performance of the TFC membranes were analyzed. These results show that the TFC membranes prepared with the PVA‐ co ‐PE nanofiber membrane can be used to filtrate different metal ions. For NaCl, Na2 SO4, CaCl2, CuCl2, CuSO4, and methyl orange solutions, the rejection rates of the TFC membrane with nonwoven polyester as the supporting layer and a nanofiber GSM of 12.8 g/m 2 are 87.9%, 93.4%, 92.0%, 93.1%, 95.8%, and 100%, respectively. This indicates the potential application of the PVA‐ co ‐PE nanofiber membrane in the preparation of nanofiltration and reverse‐osmosis TFC membranes. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46261. Abstract :